GLOBAL MARKETING: EMERGING TRENDS AND DIGITAL STRATEGIES - SYSOIEVA, Inna; TSIKHANOVSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In today’s world, globalization, digitalization, and dynamic changes in consumer behavior pose numerous challenges for businesses that require innovative approaches to marketing. The main problem is the need to adapt marketing strategies to the rapid development of technologies and growing consumer expectations. In particular, the growing influence of digital communication channels, such as social networks, video content, and e-commerce, creates new requirements for companies. At the same time, the need for personalization of offers, based on big data analytics and artificial intelligence, requires a deep understanding of individual customer needs. The article examines contemporary trends in global marketing, particularly focusing on the adoption of digital technologies that enhance customer interaction efficiency. Special attention is paid to omnichannel strategies, which ensure seamless customer experience by integrating various touchpoints such as online platforms, physical stores, and mobile applications. The use of CRM systems, artificial intelligence, and automated marketing platforms enables companies to predict customer needs more effectively, reduce response times, and create personalized offers. The study presents statistical data indicating that companies implementing omnichannel approaches report a 73% increase in customer loyalty and a 55% rise in profitability. Future research prospects include exploring blockchain technologies, metaverses, and other innovations to expand marketing capabilities. The practical value of this article lies in identifying strategies for businesses to adapt to the dynamic conditions of the global market, considering technological advancements and growing consumer expectations.